Engineering Bulk, Layered, Multicomponent Nanostructures with High Energy Density. Issue 22 (2nd May 2018) - Huang, Guangwei; Li, Xiaohong; Lou, Li; Hua, Yingxin; Zhu, Guangjun; Li, Ming; Zhang, Hai‐Tian; Xiao, Jianwei; Wen, Bin; Yue, Ming; Zhang, Xiangyi
Abstract: The precise control of individual components in multicomponent nanostructures is crucial to realizing their fascinating functionalities for applications in electronics, energy‐conversion devices, and biotechnologies. However, this control remains particularly challenging for bulk, multicomponent nanomaterials because the desired structures of the constitute components often conflict. Herein, a strategy is reported for simultaneously controlling the structural properties of the constituent components in bulk multicomponent nanostructures through layered structural design. The power of this approach is illustrated by generating the desired structures of each constituent in a bulk multicomponent nanomaterial (SmCo + FeCo)/NdFeB, which cannot be attained with existing methods. The resulting nanostructure exhibits a record high energy density (31 MGOe) for this class of bulk nanocomposites composed of both hard and soft magnetic materials, with the soft magnetic fraction exceeding 20 wt%. It is anticipated that other properties beyond magnetism, such as the thermoelectric and mechanical properties, can also be tuned by engineering such layered architectures. Abstract : A strategy is devised for simultaneous control over structural properties of constituents in bulk multicomponent nanostructures . With this strategy a bulk multicomponent nanostructure with the desired structures is created. The engineered nanostructure exhibits an unprecedentedly high energy density for this class of bulk nanocomposites composed of both hard and soft magnetic materials, with soft magnetic fractions exceeding 20 wt%.